The effects of the supply of credit on real estate prices: Venezuela as a policy laboratory - Claire Boeing-Reicher; David Pinto (Kiel Institute for the World Economy (IfW), 2016)
We identify the effects of the supply of mortgage credit on house prices, using the politicallydirected credit-targeting regime of Venezuela as quasi-natural experiment. We find a large effect of the supply of housing credit on time path of house prices (or housing Markups), with an elasticity of housing markups with respect to credit of about 0.23 under our baseline specification, and similar results under a set of alternative specifications. These estimates are close to previous panel estimates for the United States, which suggests that these estimates capture similar phenomena.
Keywords: E51; E65; R31; 330; house prices; credit supply; Venezuela; credit targeting